1997
DOI: 10.1097/00005373-199703000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Indicators of the Posttraumatic Inflammatory Response Correlate with Organ Failure in Patients with Multiple Injuries

Abstract: These data show that the degree of the initial inflammatory response corresponds with the development of posttraumatic organ failure. Besides anatomically and physiologically based trauma scores, these parameters might be used as indicators for the injury severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
83
2
18

Year Published

1998
1998
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 201 publications
(107 citation statements)
references
References 27 publications
4
83
2
18
Order By: Relevance
“…Lactate concen-trations have been correlated with the development of multiple organ dysfunction syndrome and death in trauma and sepsis. 32,33 Dogs in this study had a lower median lactate concentration and a significantly higher median blood glucose concentration than did the general population of dogs with CPV examined during a 6-month period in which the clinical trial was conducted. Because the owners of dogs enrolled in this study were required to commit to extended care and therefore considerable financial demands, this study was socioeconomically biased.…”
Section: Discussionmentioning
confidence: 83%
“…Lactate concen-trations have been correlated with the development of multiple organ dysfunction syndrome and death in trauma and sepsis. 32,33 Dogs in this study had a lower median lactate concentration and a significantly higher median blood glucose concentration than did the general population of dogs with CPV examined during a 6-month period in which the clinical trial was conducted. Because the owners of dogs enrolled in this study were required to commit to extended care and therefore considerable financial demands, this study was socioeconomically biased.…”
Section: Discussionmentioning
confidence: 83%
“…In a study of patients with multisystem trauma who had a femoral shaft fracture, Crowl et al 10 showed that early intramedullary fixation of femoral shaft fracture (less than twenty-four hours after admission) in the setting of occult hypoperfusion (serum lactate, ‡2.5 mmol/L) led to a significant increase in postoperative complications. Hypoperfusion resulting from trauma may prime the immune system for an inflammatory response if such treatment is undertaken prior to adequate resuscitation and can lead to substantial end-organ injury 61,62 . The realization of this phenomenon has led to the description of so-called ''damagecontrol orthopaedics,'' whereby definitive treatment is delayed until resuscitation of the patient has been adequately achieved 13,42,63,64 .…”
Section: Discussionmentioning
confidence: 99%
“…M any studies have demonstrated that monocyte (M ) 4 / macrophage (Mac) dysfunctions are pivotal in the development of the dysregulated inflammatory cytokine production typical of trauma patients who develop multiple organ failure and infectious complications (1)(2)(3)(4)(5)(6). Simultaneous with the often-exaggerated inflammatory response, these patients' M show depressed HLA-DR expression and a failure of Ag-presenting functions, which appears to be correlated with the development of T cell immunosuppression (7)(8)(9)(10)(11)(12)(13).…”
Section: M-csf Combined With Il-6 Inhibits M -To-idc Differentiation mentioning
confidence: 99%